Review Of The Fatigue Performance Of Stainless Steel 316L Parts Manufactured By Selective Laser Melting - Zhang, Meng (2016)
The powder bed additive manufacturing (AM) process is known to produce defects that can trigger premature fatigue failure under the service loads. Material testing on metallic AM parts thus far has focused on the static mechanical properties, although the fatigue strength is highly pertinent due to the high sensitivity to manufacturing defects. Currently, there is a lack of standardised approaches for the determination of suitable process parameters to ensure consistent acceptable quality of additively manufactured parts. Therefore, this work reviews the formation and prevention of defects in the selective laser melting (SLM) process and examines their impact the quality of stainless steel 316L parts, using the fatigue properties as the main criteria. This will aid future works on the characterisation of material against key process parameters and fatigue tests, and support the development of predictive fatigue models in later phase of the project. Ultimately, the study will contribute to the guidelines for the production and certification of metal AM components and assist manufacturers in achieving required material performance.